2016
DOI: 10.1080/08905436.2016.1198263
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Bacteriocin-Producing Lactic Acid Bacteria from Mexican Regional Cheeses and their Contribution to Milk Fermentation

Abstract: The aim of this work was to examine the biodiversity of bacteriocin-producing lactic acid bacteria from homemade cheeses produced in Veracruz (México) and assess their contribution as adjunct cultures in dairy products. Ninety-three presumptive bacteriocinogenic strains were detected by direct antagonism assays and twenty-nine out of them were active against Enterococcus faecalis NRRL-B537, Listeria innocua 062 AST, or Listeria monocytogenes ATCC19115 by the well diffusion test using cell-free supernatants, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
1
0
3
Order By: Relevance
“…These results agree with Portilla‐Vázquez et al . (2016), who found that Lactobacillus species could produce succinic acid from citric acid via the reductive pathway of the tricarboxylic acid (TCA) cycle, while acetic acid may be formed from citrate metabolism by citrate lyase. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results agree with Portilla‐Vázquez et al . (2016), who found that Lactobacillus species could produce succinic acid from citric acid via the reductive pathway of the tricarboxylic acid (TCA) cycle, while acetic acid may be formed from citrate metabolism by citrate lyase. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Esta especie (Lb. fermentum) se ha reportado en el queso artesanal Kazak (Xinjiang, China) (Li et al, 2020), queso Oaxaca (Caro et al, 2013) y quesos frescos artesanales de Veracruz, México (Portilla-Vázquez et al, 2016). Otra BAL es Lb.…”
Section: Identificación Genéticaunclassified
“…plantarum son productoras de bacteriocinas, actividad antagónica contra Entrb. faecalis, Listeria innocua o L. monocytogenes) (Portilla-Vázquez et al, 2016). Esta última, también ha registrado resistencia a los antibióticos y capacidad acidificante (Caro et al, 2013).…”
Section: Identificación Genéticaunclassified
See 1 more Smart Citation